2022
DOI: 10.3389/fmicb.2022.932224
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Investigation of Ticks From Kenyan Wildlife Reveals Diverse Microbial Pathogens and New Country Pathogen Records

Abstract: Focusing on the utility of ticks as xenosurveillance sentinels to expose circulating pathogens in Kenyan drylands, host-feeding ticks collected from wild ungulates [buffaloes, elephants, giraffes, hartebeest, impala, rhinoceros (black and white), zebras (Grévy’s and plains)], carnivores (leopards, lions, spotted hyenas, wild dogs), as well as regular domestic and Boran cattle were screened for pathogens using metagenomics. A total of 75 host-feeding ticks [Rhipicephalus (97.3%) and Amblyomma (2.7%)] collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 72 publications
1
13
1
Order By: Relevance
“…On the lower end, one failed to detect it (48) and another reported a prevalence of 5.5% (49). On the higher end, a study reported a prevalence of 45.7% (50) which is comparable to the current detected level of 37.88%. This shows that more research is required to ascertain what other factors may be affecting the prevalence of C. burnetii in ticks.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…On the lower end, one failed to detect it (48) and another reported a prevalence of 5.5% (49). On the higher end, a study reported a prevalence of 45.7% (50) which is comparable to the current detected level of 37.88%. This shows that more research is required to ascertain what other factors may be affecting the prevalence of C. burnetii in ticks.…”
Section: Discussionsupporting
confidence: 74%
“…On the lower end, one failed to detect it (48) and another reported a prevalence of 5.5% (49). On the higher end, a study reported a prevalence of 45.7% (50) which is comparable to the current detected level of 37.88%. This…”
Section: Discussionmentioning
confidence: 69%
“…We have named these as Engoha virus isolates 1-3. We also detected Trinbago virus, another member of the Flaviviridae in six Rhipicephalus tick pools from Nakaseke and Lyantonde districts, four of which were used for phylogenetic analysis (P158, P171, P172, P176; Fig 4d ), a virus first detected in Trinidad and Tobago in R. sanguineus, R. microplus, and A. ovale ticks in 2019 and more recently detected in Kenya (14). Viruses in this clade are assigned to the Pestiviruslike group and species differ by 15% in the polyprotein amino acid sequence.…”
Section: Resultsmentioning
confidence: 94%
“…Interestingly, out of the 65 CDV-positive dogs, only in 20 animals was CDV the only pathogen identified, with CPV2 and CCoV being frequently detetced in co-infection. Co-infections are frequently found in dogs [ 65 , 66 ] and the extent of this phenomenon has been revealed by the adoption of syndromic diagnostics (i.e., multi-screening of samples against a recognized panel of pathogens) [ 67 ] and, more recently, by metagenomic investigations in domestic and wildlife animals [ 68 , 69 ]. We cannot rule out that concomitant changes in the epidemiology of viruses with immune-suppressive activity may also occur in the local canine population, amplifying the magnitude of the CDV epidemic.…”
Section: Discussionmentioning
confidence: 99%